Apply PLC to Control 3-Axis Machines - Cheypoca, Thepjit; Thaiyai, In; Maneerat, Noppadol; Narkthewan, Athasart (My University, 2025)
This report presents a method of using PLC (Programable Logic Control) to control the work instead of the 3-Axis machine position controller. PLC is popularly used in various types of control systems. It has a lot of control capabilities, is efficient, stable, durable, easy to use, and cheap. It is the use of commands to control the work of all 3 axes, 2 axes, and 1 axle. The commands used for moving in both straight lines and curves, and there are other devices that need to be controlled together with the machine that is being controlled.
Keywords: motion control; PLC; Programmable Logic Controller; S7-1200